The Cauchy problem for the Korteweg-De Vries equation in Bourgain’s spaces - Rojas, Cesar Loza (2017)
In this paper, we study Cauchy’s problem to the Korteweg-De Vries equation in Hs with s > -3/4 . For this purpose we use the Bourgain spaces, Xs;b; and we get good local formulation to the Cauchy problem.